Applied High-Speed Plate Penetration Dynamics - Ben-Dor, Gabi; Dubinsky, Anatoly; Elperin, Tov (Solid Mechanics and Its Applications, 2006)
High-speed impact dynamics is of interest in the fundamental sciences, e.g., astrophysics and space sciences, and has a number of important applications in military technologies, homeland security and engineering. When compared with experiments or numerical simulations, analytical approaches in impact mechanics only seldom yield useful results. However, when successful, analytical approaches allow us to determine general laws that are not only important in themselves but also serve as benchmarks for subsequent numerical simulations and experiments. The main goal of this monograph is to demonstrate the potential and effectiveness of analytical methods in applied high-speed penetration mechanics for two classes of problem. The first class of problem is shape optimization of impactors penetrating into ductile, concrete and some composite media. The second class of problem comprises investigation of ballistic properties and optimization of multi-layered shields, including spaced and two-component ceramic shields. Despite the massive use of mathematical techniques, the obtained results have a clear engineering meaning and are presented in an easy-to-use form. One of the chapters is devoted solely to some common approximate models, and this is the first time that a comprehensive description of the localized impactor/medium interaction approach is given. In the monograph the authors present systematically their theoretical results in the field of high-speed impact dynamics obtained during the last decade which only partially appeared in scientific journals and conferences proceedings.